Penentuan Kriteria Pemilihan Vendor Pengadaan Chemical Water Treatment Menggunakan Metode Analytical Hierarchy Process di Perusahaan Outsourcing - Fazabahy, Ramzy Aqilla; Vikaliana, Resista; Aryani, Fika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
PT Integra Energi Group is a company engaged in outsourcing, focusing on the oil and gas sector. As a company, PT Integra Energi Group requires goods and services to support its operational activities, so the role of procurement is very important, and the procurement team needs to ensure that the procurement process runs efficiently. To support an efficient procurement process, it is necessary to select vendors effectively and objectively. Therefore, it is essential to determine the priority criteria considered in vendor selection using the Analytical Hierarchy Process (AHP) method. AHP facilitates the comparison and evaluation of multiple criteria. Based on this, the objective of this study is to determine the criteria and sub-criteria at PT Integra Energi Group in the selection of procurement vendors and to determine the priority of criteria using the Analytical Hierarchy Process (AHP) method. Based on interviews and questionnaires with five respondents directly involved in the procurement process at PT Integra Energi Group, it can be concluded that there are six criteria and four sub-criteria in goods procurement at PT Integra Energi Group. Weighting was then performed using Expert Choice software with the paired comparison method. In the procurement of goods at PT Integra Energi Group, the criterion with the highest weight is quality, with a weight of 0.389. The second most important criteria are price, delivery, safety, ethics, and vendor location. The company can use the criteria and sub-criteria described in this study for vendor selection, considering the level of importance to ensure that vendor selection is conducted objectively and systematically.